2023
DOI: 10.1002/acm2.14015
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of deep learning‐based knowledge‐based planning methods for 3D dose distribution prediction of head and neck

Abstract: PurposeIn this paper, we compare four novel knowledge‐based planning (KBP) algorithms using deep learning to predict three‐dimensional (3D) dose distributions of head and neck plans using the same patients’ dataset and quantitative assessment metrics.MethodsA dataset of 340 oropharyngeal cancer patients treated with intensity‐modulated radiation therapy was used in this study, which represents the AAPM OpenKBP – 2020 Grand Challenge dataset. Four 3D convolutional neural network architectures were built. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“… 12 , 25 , 26 As a kind of typical transformers-based DL model, UNETR has never been used in dose prediction. 27 Research from Osman et al 28 showed that U-Net, attention U-Net, residual U-Net, and attention Res U-Net for H&N plans from OpenKBP-Grand Challenge data 7 had an almost comparable performance for voxel-wise dose prediction. Inspired by Osman et al's research, 28 we compared the 3D U-Net and its typical variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 25 , 26 As a kind of typical transformers-based DL model, UNETR has never been used in dose prediction. 27 Research from Osman et al 28 showed that U-Net, attention U-Net, residual U-Net, and attention Res U-Net for H&N plans from OpenKBP-Grand Challenge data 7 had an almost comparable performance for voxel-wise dose prediction. Inspired by Osman et al's research, 28 we compared the 3D U-Net and its typical variants.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Research from Osman et al 28 showed that U-Net, attention U-Net, residual U-Net, and attention Res U-Net for H&N plans from OpenKBP-Grand Challenge data 7 had an almost comparable performance for voxel-wise dose prediction. Inspired by Osman et al's research, 28 we compared the 3D U-Net and its typical variants. Our results show that the 4 DL models have high capability in accurately predicting 3D dose distributions for cervical cancer VMAT plans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other types of networks, such as Resnet ( 27 , 29 , 30 ) and GAN ( 31 33 ), are also used for dose prediction. So far, the deep U-net-like architecture and its variants with various types of residual or dense blocks become the mainstream structure for dose prediction ( 34 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the successful applications of deep learning models in predicting dose distribution for many primary tumor sites such as the lung ( 25 , 26 ), head-and-neck ( 23 , 28 , 33 , 34 ), and prostate ( 21 , 35 ), it is interesting to investigate this application for brain metastasis. In the study, a deep U-net architecture ( 30 ), previously successfully applied to predict dose distribution for head-and-neck cancer patients, is used as the base model in predicting the dose distribution of the VMAT plan for brain metastasis.…”
Section: Introductionmentioning
confidence: 99%